Sistem Informasi Akademik Menggunakan Rapid Application Development Pada SDIT Insan Qur’ani Sumbawa Berbasis Web - Nora Dery Sofya (AMIK STIEKOM SUMATERA UTARA, 2023)
SDIT Insan Qur'ani is an elementary school with an increasing number of students every year. The administrative process that runs and the learning process that is carried out at SDIT Insan Qur'ani still uses paper media for administrative processes which will then be re-entered into the Microsoft Excel number processor. To support the administrative process and teaching and learning process with an ever-increasing number of students, an academic information system is needed that can support better work. This study aims to create an Academic Information System using Rapid Application Development (RAD) on Web-Based SDIT Insan Qur'ani. Research using the RAD method is divided into five stages, business modeling, data modeling, process modeling, application development, and testing. The system design process is carried out using the Unified Modeling Language (UML) model, as well as using the MySQL database and the Hypertext Processor (PHP) programming language. This study uses the CodeIgniter framework and applies black-box testing to the academic information system that is created. The results of this study are 11 features that can be used to support administrative processes and teaching and learning processes.